Total synthesis of natural (−)- and unnatural (+)-Melearoride A. Issue 10 (7th March 2019) - Reed, Carson W.; Fulton, Mark G.; Nance, Kellie D.; Lindsley, Craig W.
Graphical abstract: Highlights: First total synthesis of (−)-Melearoride A. Total synthesis of (+)-Melearoride A. A concise 13 step synthesis from chiral pool starting materials. High yielding RCM to close the 13-membered macrocycle. Abstract: This communication details the first total synthesis of the 13-membered macrolide, (−)-Melearoride A, as well as unnatural (+)-Melearoride A. The synthesis features a concise 13 step synthesis (11 steps longest linear sequence) that offers flexible stereo-control and multiple opportunities for unnatural analog synthesis to delve into antifungal SAR. The route features a cuprate addition, an Evans asymmetric alkylation, and a ring-closing metathesis (RCM) to close the 13-membered macrocyclic core.